2019
DOI: 10.3389/fnins.2018.01051
|View full text |Cite
|
Sign up to set email alerts
|

Differential Genetic Effect of the Norepinephrine Transporter Promoter Polymorphisms on Attention Problems in Clinical and Non-clinical Samples

Abstract: Among the monoaminergic modulatory neurotransmitters, norepinephrine is involved in task orienting, hence noradrenergic genetic variants have been studied in connection to attentional processes. The role of this catecholamine system is also highlighted by the selective norepinephrine transporter blocking atomoxetine, which has proved to be effective in the pharmacological treatment of Attention Deficit Hyperactivity Disorder (ADHD). In the present genetic association study three single nucleotide polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Meanwhile for MCG, this linear relationship between brain volume and number of risk C alleles was not detected in this study. An inverted U-shaped regulatory effect that catecholamines, including dopamine and NE, has a cognitive function in attention deficit hyperactivity disorder patients has been proposed in previous studies [ 36 ]. Thus, we speculate that, unlike SPG, the cingulate gyrus may be subject to the nonlinear regulatory effect of NE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile for MCG, this linear relationship between brain volume and number of risk C alleles was not detected in this study. An inverted U-shaped regulatory effect that catecholamines, including dopamine and NE, has a cognitive function in attention deficit hyperactivity disorder patients has been proposed in previous studies [ 36 ]. Thus, we speculate that, unlike SPG, the cingulate gyrus may be subject to the nonlinear regulatory effect of NE.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this reduction in volume is potentially associated with the sustained vigilance and alertness associated with PTSD [ 39 ]. The NE system’s main function involves regulating alertness, while it also projects to various cortical regions including the frontal lobe [ 36 ]. Therefore, we reason that the differences in SLC6A2 gene expression could have an influence on the volume of frontal gray matter in patients with PTSD, through affecting the amount of NE production and leading to PTSD-related alertness symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Although these might be the most common expected alleles in Chinese patients, one cannot exclude the possibility of some rare alleles contributing to miss assignment of predicted CYP2D6 phenotype, especially given that comparison of clinical response between EMs and IMs was considered in this study. In addition to CYP2D6, variations in atomoxetine response have also been examined with its metabolizing enzyme, like CYP2C19 [ 45 , 46 ] and its pharmacodynamic target, like SLC6A2 [ 37 , 47 ]. The potential effects of these genetic variations were not incorporated in our study either.…”
Section: Discussionmentioning
confidence: 99%
“…The inverted gene effects of patients and controls have been observed for other genes. For example, an inverted U-shape effect of the norepinephrine transporter (NET) gene SNPs was found in patients with attention deficit hyperactivity disorder (ADHD), with the T allele carrier having lower attention problem scores compared to patients with the AA genotype, whereas T allele carriers in the community sample had more attention problem ( Nemoda et al, 2018 ). A similar U-shaped genetic effect is observed in the COMT gene in Parkinson’s disease ( Fallon et al, 2013 ), during attentional formation processing, Val homozygotes showed higher dorsolateral prefrontal cortex activity than Met carriers, while an opposite pattern was observed in healthy older individuals.…”
Section: Discussionmentioning
confidence: 99%